IL-1 as a key inflammatory regulator in autoinflammatory diseases - Goldbach-Mansky, Raphaela (Henry Stewart Talks, 2011)
Understand the concept of autoinflammatory syndromes and typical clinical features, Understand the role of IL-1 on the phenotype of two IL-1 mediated autoinflammatory syndromes: NOMID and DIRA, Understand the impact of the discovery of the role of IL-1 in rare diseases, The understanding of the pathogenesis of common diseases such as gout and Type II diabetes